Extracellular protons titrate voltage gating of a ligand-gated ion channel - Martínez-François, Juan Ramón (The Rockefeller University Press, 2010)
Cyclic nucleotide–gated channels mediate transduction of light into electric signals in vertebrate photoreceptors. These channels are primarily controlled by the binding of intracellular cyclic GMP (cGMP). Glutamate residue 363 near the extracellular end of the ion selectivity filter interacts with the pore helix and helps anchor the filter to the helix. Disruption of this interaction by mutations renders the channels essentially fully voltage gated in the presence of saturating concentrations of cGMP. Here, we find that lowering extracellular pH makes the channels conduct in an extremely outwardly rectifying manner, as does a neutral glutamine substitution at E363. A pair of cysteine mutations, E363C and L356C (the latter located midway the pore helix), largely eliminates current rectification at low pH. Therefore, this low pH-induced rectification primarily reflects voltage-dependent gating involving the ion selectivity filter rather than altered electrostatics around the external opening of the ion pore and thus ion conduction. It then follows that protonation of E363, like the E363Q mutation, disrupts the attachment of the selectivity filter to the pore helix. Loosening the selectivity filter from its surrounding structure shifts the gating equilibrium toward closed states. At low extracellular pH, significant channel opening occurs only when positive voltages drive the pore from a low probability open conformation to a second open conformation. Consequently, at low extracellular pH the channels become practically fully voltage gated, even in the presence of a saturating concentration of cGMP.